Сербский cтoлпный апракос Равулы (ок. 1353 г.): происхождение, особеннocти языка, cтруктура - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2003)
The paper presents a description of a Serbian (Raška school) manuscript (Dublin, The Chester Beatty Library, W 158), previously kept in the National Library of Serbia in Belgrade (No. 213), where it formed a single volume with the Octoechos of 1353 (written by hieromonk Daniel in the church of St. Paraskeva the Martyr, located in the Siriniči district near Prizren (the Octoechos part of the volume is now kept in the Houghton Memorial Library at Harvard, Cod. Slav. 2).The article gives a survey of the four manuscripts known to be written by monk Ravula, and argues that the Dublin codex was also written by him at the same place (in the church of St. Paraskeva in the village of Sredska) and time as the Octoechos of 1353. The contents of the Dublin manuscript can be described as a columnar lectionary, containing readings from both the Gospels and the Acts and Epistles. The article presents the case that when it was kept in Belgrade, the Ravula Lectionary must have contained nearly twice as many folia as it contains now, and the analysis reconstructs the structure of its lost portion. A reconstruction of the prehistory of the Dublin codex is also presented.